Pemanfaatan SIG Untuk Menganalisis Daerah Rawan Banjir Kabupaten Sukabumi Menggunakan Model Complete Mapping Analysis - Mohammad Alexander Agung putera Gustaf; lham Badaruddin Mataburu (Universitas Negeri Gorontalo, 2025)
Flooding in Sukabumi District is influenced by various factors, including heavy rainfall, land use change, slope, and topographic characteristics. This research utilizes Geographic Information System (GIS) approach and Complete Mapping Analysis (CMA) model to map flood vulnerability. (CMA) model to map the level of flood vulnerability. The parameters analyzed include rainfall, topographic wetness index (TWI), land use, slope, soil type, and elevation. The results of the analysis show that land use has the highest weight in influencing flood events, followed by TWI and slope. Areas with high flood vulnerability tend to be located in lowlands with gentle slopes, such as Warung Kiara and Bantargadung sub-districts. A decrease in water flow velocity in plain areas increases the potential for inundation or flooding. This analysis analysis provides a comprehensive overview of the factors that influence flood vulnerability, which can be used for disaster mitigation planning, such as land use management, drainage systems, and conservation of water catchment areas. water catchment areas.